Dermal Autografts in Breast Reconstruction: A Review of Past and Current Trends. Issue 5 (May 2020) - Davis, Claire; Boyd, Carter; Mateo de Acosta Andino, David A.; Kumbla, Pallavi A.; Sanchez, Ruston J.; Kurapati, Srikanth; King, Timothy W.; de la Torre, Jorge I.
Abstract : Abstract: Breast cancer affects 1 in 8 women. As the treatment of breast cancer evolves, breast reconstruction does as well. Implant-based reconstructions are increasing, leading to increased use of acellular dermal matrix (ADM) for better implant positioning. Acellular dermal matrices are derived from cadaveric skin and are processed to be immunologically inert. However, ADM can be costly and can have complications such as seroma and infection. This has led to the development of dermal autografts. These were first used in postmastectomy breast reconstruction in women with redundant breast skin that was deepithelialized and used for lower pole coverage of tissue expanders and implants. This evolved into harvesting dermal autografts from the abdomen. Later studies evaluated the use of meshed dermal autografts. Histological analysis of ADM versus dermal autografts shows that there are increased vessels within dermal autografts compared with ADM. This potentially contributes to the decreased complication rate seen with autografts. In addition, one study showed equivalent results in aesthetic outcomes and capsular contracture between ADM and dermal autograft. Analysis of cost has shown that ADM is significantly more costly than harvesting a dermal autograft. Physician reimbursement is also higher for dermal autografts. This review article seeks to summarize key studies that highlight the feasibility of using dermal autografts in breast reconstruction.